Does Age Impact the Clinical Presentation of Adult Women Seeking Specialty Eating Disorder Treatment?. Issue 9 (September 2020) - Henriksen, Christine A.; Mackenzie, Corey S.; Fergusson, Patricia; Bouchard, Danielle R.
Abstract : Abstract: Recent evidence suggests that eating disorders (EDs) are becoming increasingly common in older women. Previous research examining differences between younger and older women with EDs has been mixed, making it unclear whether older women with EDs represent a distinct group. We sought to determine whether there are age differences in the clinical presentation of women seeking specialty treatment for an ED. We examined the linear relationship between age and clinical constructs among adult women ( N = 436) diagnosed with a Diagnostic and Statistical Manual of Mental Disorders, 4th Edition, ED. Across analyses, there was no impact of age on most measures of ED symptoms, comorbid psychopathology, self-esteem, quality of life, and motivation to change. However, older age was associated with fewer interoceptive awareness difficulties, maturity fears, anxiety symptoms, and body image concerns. These findings suggest that the clinical presentation of older ED cases is largely similar, although somewhat less severe than in younger women. The implications of this research for future research and treatment are discussed.